Memory and Memorialization in Bosnia Herzegovina - Jahić, Ahmed; Eyüce, Özen (ICONARCH International Congress of Architecture and Planning, 2017)
The paper will focus on monuments and memorials, the two being the main architectural agents of social and individual remembrance. How was the design and the realization of monuments and memorials and our position in regard to them affected by the transitory nature of time which every manmade object is subjected to? Because of its fundamental place in the definition of memorials, no study of them can be done without including memory. Our modern obsession with forgetting also made us question and eventually completely overturn the long-standing concept of memory as a database of information of the past. While the ideas of grandeur and glory have been replaced with democracy, the archetypal form of monuments and memorials, once celebrating heroes and rulers, are nearly abandoned today, the memorial culture has brought us to the conclusion that by the act of investing memories in an object or so-called prosthetic memory we may be dispersing them at the same time. Bosnia and Herzegovina, with its turbulent past, having been through different forms of government, from imperial to socialist and finally democratic, is a fertile ground for researching the changes in memorialization practices. Establishing the major turning point and paradigm shifts in both of the subjects, the paper aims to identify how and to what extent did the changes in society, its perspective on memory, and who or what is being remembered affect form, scale, shape, spatial organization, symbols, materials and other important aspects of post-war architectural memorialization.